Pengaruh Promosi Melalui Instagram Terhadap Keputusan Pembelian Di Food Court - Elin Lininati (Universitas Tarumanagara, 2019)
This research aims to analyse the effect of promotion through social media, using 4C’s model (context, communication, collaboration, connection) toward consumer purchasing decisions with AIDCA concept in food court. This research was conducted using quantitative data from a questionnare that containing 27 grains of questions and distributed to 1079 respondents. The respondents was Instagram’s user in Indonesia and have been purchase in food court. The model equations are processed using SPSS version 2.0. Analysis of data used in this study is to test hypotheses using validity and reliability testing. A hypotesis based on the results obtained that context, communication, collaboration, connection have a positive effect toward purchasing decision in food court. Then, the result was context, communication, collaboration, connection have a positive effect toward purchasing decision. Even thought, variable communication has positif effect, it does not significant toward purchasing decision. Overall purchasing decision was correlated by context, communication, collaboration, connection even is about 28,9%. Meanwhile, some 71,1% was correlated by another factor such as marketing mix; product, place, price, and also another promotion mix. Researcher suggest that each food court who have Instagram’s account, take attention to their followers, morever by comment, which is customer need respond. Food courts’ managers should pay attenton about content that they created, the content should be informative and always up to date.